HSP90 Inhibitors Modulate SARS-CoV-2 Spike Protein Subunit 1-Induced Human Pulmonary Microvascular Endothelial Activation and Barrier Dysfunction - Colunga Biancatelli, Ruben Manuel Luciano; Solopov, Pavel A.; Gregory, Betsy; Khodour, Yara; Catravas, John D. (Frontiers in Physiology, 2022)
Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has caused more than 5 million deaths worldwide. Multiple reports indicate that the endothelium is involved during SARS-Cov-2 related disease (COVID-19). Indeed, COVID-19 patients display increased thrombophilia with arterial and venous embolism, and lung microcapillary thrombotic disease as major determinants of deaths. The pathophysiology of endothelial dysfunction in COVID-19 is not completely understood. We have investigated the role of the subunit-1 of the SARS-CoV-2 Spike protein (S1SP) in eliciting endothelial barrier dysfunction, characterized dose- and time-relationships and tested the hypothesis that Heat Shock Protein 90 (HSP90) inhibitors would prevent and repair such injury. S1SP activated (phosphorylated) IKBα, STAT3, and AKT, and reduced the expression of intercellular junctional proteins, occludin and VE cadherin. HSP90 inhibitors (AT13387 and AUY-922) prevented endothelial barrier dysfunction and hyperpermeability and reduced IKBα and AKT activation. The two inhibitors also blocked S1SP-mediated barrier dysfunction and loss of VE cadherin. These data suggest that Spike protein subunit 1 can elicit, by itself, direct injury to the endothelium and suggest a role of HSP90 inhibitors in preserving endothelial functionality.